1998
DOI: 10.1046/j.1365-2036.1998.00377.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for impaired assimilation and increased colonic fermentation of protein, related to gastric acid suppression therapy

Abstract: Gastric acid suppression therapy hampers protein assimilation and may promote protein malabsorption. Gastric digestion is likely to play a substantial role in overall protein assimilation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(58 citation statements)
references
References 33 publications
2
53
0
1
Order By: Relevance
“…The production of both compounds therefore depends on the delivery of amino acids to the colon and on the activity of colonic bacteria, which may ascend to the small bowel in uremic patients (16). Studies in normal individuals have shown that the production of p-cresol can be increased by dietary protein loading and medications that impair protein digestion and decreased by maneuvers that increase the delivery of carbohydrates and fiber to the colon (13,(17)(18)(19)(20), but we could not identify differences in protein intake, medications, or bowel history that would account for the lower indican and PCS removal observed in PD patients without residual renal function. Tracer studies may ultimately be required to identify the cause of reduced indican and PCS appearance in these patients.…”
Section: Discussionmentioning
confidence: 42%
See 1 more Smart Citation
“…The production of both compounds therefore depends on the delivery of amino acids to the colon and on the activity of colonic bacteria, which may ascend to the small bowel in uremic patients (16). Studies in normal individuals have shown that the production of p-cresol can be increased by dietary protein loading and medications that impair protein digestion and decreased by maneuvers that increase the delivery of carbohydrates and fiber to the colon (13,(17)(18)(19)(20), but we could not identify differences in protein intake, medications, or bowel history that would account for the lower indican and PCS removal observed in PD patients without residual renal function. Tracer studies may ultimately be required to identify the cause of reduced indican and PCS appearance in these patients.…”
Section: Discussionmentioning
confidence: 42%
“…It is also possible that the remnant kidney is able to degrade these substances and continues to remove them from the circulation even when urine output has practically ceased. In general, however, removal rates for indican and PCS have been considered to reflect the production of these solutes, and we think it most likely that indican and PCS production were reduced in the PD patients who had lost residual function (13)(14)(15). Both indican and PCS are made in the colon, where bacteria act on tryptophan and on phenylalanine and tyrosine to produce indole and p-cresol, which are then conjugated with sulfate.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study demonstrated that CAG-positive asymptomatic middle-aged subjects, as determined by the serum PG levels of PG I ≤70 ng/ml and a PG I/II ratio of ≤3.0, were found to have larger colonic microflora compared to CAG-negative subjects, with an increase in 83% of the genera or groups comprising intestinal microflora (6). Gastric acid reduction is also reported to lead to increases in unabsorbed nutrients in the lower intestine, due to impaired gastric protein digestion (38), therefore leading to the alteration of the microflora with an increase in bacterial species utilizing these malabsorbed nutrients. Certain metabolites derived from the bacterial fermentation of malabsorbed proteins are also likely to be involved in the etiopathogenesis of colonic disorders, including epithelial neoplasia (39).…”
Section: Discussionmentioning
confidence: 98%
“…79 It should be noted that impaired protein assimilation has been described in patients treated with omeprazole. 80 The improvement in fat digestion seen with PES may be at the cost of decreased efficiency of protein digestion with the use of acid suppression. This was demonstrated in a prospective crossover study where the use of acid suppression with PES was associated with a marked decrease in the fat-protein content ratio in stool, 81 suggesting an increase in fat absorption with a decrease in protein absorption.…”
Section: Role Of Simultaneous Acid Supressionmentioning
confidence: 99%